Mapeamento da vulnerabilidade natural à perda de solos na sub bacia do Rio Cascavel, município de Cascavel, Paraná - Corti, Adrielen Moraes (2016)
The environmental researches and their conditions encourage sustainable practices of environmental management. The natural vulnerability to loss of soil is associated with the natural soil conditions and their way of operating. This study aimed to develop natural loss vulnerability maps of the soil inthe area of Cascavelriver sub basin, and such maps are able to associate the natural loss of soil data with the studied environmental components (geology, geomorphology, pedology, climate, vegetation). The methodology used in this study was based on the approach of CREPANI et al. (2001), which combines the environmental attributes (geology, soil science, geomorphology, vegetation, climate) of Basic Territorial Units (UTB's), through the use of geospatial technologies, digital imaging and data analysis, integrating such data resulting in a vulnerability map loss of land. From the obtainedresults, it was observed that the vulnerability of the area studied ranged from stablemoderately to stable/vulnerablemoderately. The study serves as a tool for analysis and interpretation of soil conditions of the area that has relevant characteristics to several urban centers, which can contribute considerably in the environmental management and planning territorial areas.